Benefits of energy storage systems and its potential applications in Malaysia: A review - Gan, Chin Kim; Sardi, Junainah; Tee, Wei Hown (Elsevier Ltd, 2023)
Energy storage systems (ESSs) play a pivotal role in improving and ensuring the performance of power systems, especially with the integration of renewable energy sources. This is evident from the exponential growth of ESS demand in recent years. The global energy storage capacity is expected to exceed 1000 GW by 2040. In Malaysia, it is predicted that there will be rapid growth of ESSs in line with the goal to achieve the renewable energy penetration target of 31 % by 2025. The growth of renewable energy in Malaysia is mainly driven by solar energy, owing to its strategic location in the tropics. In this regard, ESSs are seen as the key enabler that can promote solar hosting in Malaysia by alleviating the technical issues arising from their integration. In this study, a comprehensive review on the benefits of ESSs in power systems is first presented and the research gap associated with ESS-solar photovoltaic integration is highlighted. Subsequently, the key opportunities and applicability of ESSs in Malaysia's power systems are identified and discussed. Furthermore, the potential development phases of ESSs are classified for the period from 2020 to 2035, considering the renewable energy development scenarios in Malaysia. This research can serve as an information resource for power utility companies as well as researchers on the opportunities of future ESSs development in Malaysia.